2017
DOI: 10.1083/jcb.201704068
|View full text |Cite
|
Sign up to set email alerts
|

Activity-dependent trafficking of lysosomes in dendrites and dendritic spines

Abstract: How are membrane proteins in distal dendrites degraded by the lysosome? Goo et al. provide the first evidence that lysosomes are positioned locally at dendritic spines in an activity-dependent manner to facilitate the remodeling of synapses through local degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
159
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(178 citation statements)
references
References 43 publications
12
159
0
Order By: Relevance
“…The processive myosins V and VI are known to mediate cargo trafficking in spines. Since lysosomes can be found both in dendrites and in dendritic spines (Goo et al , ), we asked whether lysosomes are associated with myosins and whether this contributes to stalling at actin‐rich loci within dendrites. Imaging of fixed lysosomes, enriched from rat cortex and hippocampus, confirmed the presence of the lysosomal markers LAMP1 and LysoTracker (Fig A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processive myosins V and VI are known to mediate cargo trafficking in spines. Since lysosomes can be found both in dendrites and in dendritic spines (Goo et al , ), we asked whether lysosomes are associated with myosins and whether this contributes to stalling at actin‐rich loci within dendrites. Imaging of fixed lysosomes, enriched from rat cortex and hippocampus, confirmed the presence of the lysosomal markers LAMP1 and LysoTracker (Fig A).…”
Section: Resultsmentioning
confidence: 99%
“…Plasticity and stability of synaptic contacts rely on several factors, including transport and delivery of proteins and mRNA from the soma, local dendritic protein synthesis, surface diffusion of membrane proteins, recycling of synaptic proteins via the dendritic secretory trafficking system, and controlled disposal of “aged” molecules mediated by lysosomes, autophagosomes, and the proteasomal system (Hanus & Schuman, ; Mikhaylova et al , ; Bowen et al , ; Goo et al , ; Nirschl et al , ; Penn et al , ; Seipold et al , ). Various secretory trafficking organelles are present along dendrites and help to regulate the protein pool required for potentiation and stabilization of specific synaptic contacts (van Bommel & Mikhaylova, ).…”
Section: Introductionmentioning
confidence: 99%
“…Using compartmentalized rat superior cervical ganglion (SCG) neuronal cultures, they observed a significant increase of LAMP2 protein exclusively in the distal axons on nerve growth factor (NGF) stimulation (Frampton et al, 2012). Recruitment of lysosomes to dendritic spines in an activity-dependent manner was also recently reported (Goo et al, 2017). These observations suggest that the abundance of lysosomes, and perhaps lysosomal degradation, is regulated locally at distal axon terminals, and possibly independently from lysosomes at the cell body [ Fig.…”
Section: Local Membrane Protein Degradation At Synapsesmentioning
confidence: 96%
“…Similar to the proteasomal degradation machinery, membrane degradation machinery has been observed both at axon terminals and near or in dendritic spines (Frampton et al, ; Goo et al, ). Frampton et al () showed the abundance of proteins lysosomal‐associated membrane protein 2 (LAMP2) and microtubule‐associated protein 1 light chain 3 (LC3) in axons and axon terminals, suggesting that lysosomes and autolysosomes are located at axon terminals.…”
Section: Where Are Membrane Proteins Degraded In Neurons?mentioning
confidence: 99%
See 1 more Smart Citation